An evaluation by rat colon anastomosis of the efficacy of fibrin glue derived from snake venom - Leite, C.v.s. [UNESP]; Naresse, L.e. [UNESP]; Arantes, H.l.; Lopes, A.f.; Thomazini-santos, I.a. [UNESP]; Giannini, M.j.s [UNESP]; Mercadante, M.c. [UNESP]; Barraviera, B. [UNESP]; Kobayasi, S. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2000)
The objective of this study was to evaluate the efficacy of fibrin adhesive made up of snake venom and bubaline fibrinogen by rat colon anastomosis. Eighty rats were randomly assigned into 2 experimental groups: GI control (anastomosis with extramucous interrupted suture) and GII (repair suture + fibrin glue). The animals were studied at the following 4 times: T0 – preoperative, T1 – 7th day postoperative, T2 – 14th day postoperative, and T3 – 21 st day postoperative. The macroscopic characteristics of the intestinal segment open and closed anastomosis and the bursting strength of the anastomosed segments were observed at each of the above times. The results showed that the anastomosed segments coapted and there was no difference in the bursting strength values between the 2 groups. There was a decrease in the bursting strength values up until the 7 th day postoperative in both groups with its progressive increase at the other times. Although important experimental studies using large animals are needed for a better evaluation of tissue repair processes, this adhesive may become a valuable tool for use in anastomosis.
Keywords: Fibrin glue; experimental healing; bursting strength; experimental anastomosis; snake venom; colon anastomosis